Novel ALDH5A1 variants and genotype: Phenotype correlation in SSADH deficiency. (10th November 2020) - DiBacco, Melissa L.; Pop, Ana; Salomons, Gajja S.; Hanson, Ellen; Roullet, Jean-Baptiste; Gibson, K. Michael; Pearl, Phillip L.
Abstract : Objective: To determine genotype–phenotype correlation in succinic semialdehyde dehydrogenase (SSADH) deficiency. Methods: ALDH5A1 variants were studied with phenotype correlation in the SSADH natural history study. Assignment of gene variant pathogenicity was based on in silico testing and in vitro enzyme activity after site-directed mutagenesis and expression in HEK293 cells. Phenotypic scoring used a Clinical Severity Score (CSS) designed for the natural history study. Results: Twenty-four patients were enrolled (10 male, 14 female, median age 8.2 years). There were 24 ALDH5A1 variants, including 7 novel pathogenic variants: 2 missense, 3 splice site, and 2 frameshift. Four previously reported variants were identified in >5% of unrelated families. There was a correlation with age and presence ( p = 0.003) and severity ( p = 0.002) of epilepsy and with obsessive-compulsive disorder (OCD) ( p = 0.016). The median IQ score was 53 (Q25–Q75, 49–61). There was no overall correlation between the gene variants and the CSS, although a novel missense variant was associated with the mildest phenotype by CSS in the only patient with a normal IQ, whereas a previously reported variant was consistently associated with the most severe phenotype. Conclusions: Seven novel pathogenic and one previously unpublished benign ALDH5A1 variants were detected. There is an age-dependent association with worsening of epilepsy and presence of OCD in SSADH deficiency. Overall, there does not appear to be a correlation between genotype and phenotypic severity in this cohort of 24 patients. We did find a suspected correlation between a novel pathogenic missense variant and high functionality, and a previously reported pathogenic missense variant and maximal severity.